The effectiveness of using virtual reality technology on learning the jump-shot skill in basketball - Mohammad Zamzami (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2020)
The aim of this study is to investigate the effectiveness of using Virtual Reality (VR) technology in learning the skill of jump-shot in basketball. Participants were 45 new volunteer students from the Department of Physical Education at Umm Al-Quran University. They had no experience in basketball and jump-shot in particular. They were divided into three groups, control group, real training group, and VR training group. Pre and post-tests were applied on the three groups to have a comparison between them. In the VR training group, we used the Virtual Reality headset device (HTC Vivek) to teach them the jump-shot in basketball. The scores were analyzed by using the One-Way ANOVA to measure their performance. Results showed a significant improvement in the level of performance for the jump-shot skill in the real training group and the VR group. While no significant improvement was noticed in the control group. Also, there was no significant differences between the real training and VR training group in post-test at the level of p=0.05 in jump-shot for the basketball skill. The results motivated faculty members in colleges of physical education in Saudi universities to take advantage of modern technological means. Making it as one of the new methods in teaching practical courses and conducting more research to identify the impact of using modern technology in learning.